Pengaruh Kepemimpinan Kepala Sekolah dan Supervisi Akademik Eksternal terhadap Kinerja Guru di Gugus Neuheun Kabupaten Aceh Besar - Amrullah, Amrullah; Akmaluddin, Akmaluddin; Novita, Rita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine the influence of school principal leadership and external academic supervision in public elementary school education units in the Neuheun Cluster, Aceh Besar Regency. This study uses a quantitative approach. The subjects of this research consisted of school principals, deputy principals, supervisors and teachers in the Neuheun State elementary school cluster. Data collection techniques use observation and questionnaires. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this research are that there is a positive influence of principal leadership on teacher performance with a strong correlation level of 0.696 and external academic supervision of supervisors has a high correlation with a percentage of 85.45%, on teacher performance at Neuheun elementary school. Aceh Besar Regency school cluster. From these results it can be concluded that there is an influence of the principal's leadership and external academic supervision on teacher performance at the Gugus Neuheun Aceh Besar elementary school